2008
DOI: 10.1371/journal.pone.0003237
|View full text |Cite
|
Sign up to set email alerts
|

The Fastest Flights in Nature: High-Speed Spore Discharge Mechanisms among Fungi

Abstract: BackgroundA variety of spore discharge processes have evolved among the fungi. Those with the longest ranges are powered by hydrostatic pressure and include “squirt guns” that are most common in the Ascomycota and Zygomycota. In these fungi, fluid-filled stalks that support single spores or spore-filled sporangia, or cells called asci that contain multiple spores, are pressurized by osmosis. Because spores are discharged at such high speeds, most of the information on launch processes from previous studies has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 19 publications
5
64
0
Order By: Relevance
“…Taphonomic studies demonstrate that coprophilous fungal spores do not travel far from their source (Raper and Bush 2009), with dispersal often limited to B2.5 m from the fruiting body (Ingold 1971;Yafetto et al 2008). Spores released from fungi growing on dung within the renvall (AKK D) might not arrive at AKK C, 15 m from the annex boundary.…”
Section: Coprophilous Fungal Spores As Indicators Of Land Usementioning
confidence: 99%
“…Taphonomic studies demonstrate that coprophilous fungal spores do not travel far from their source (Raper and Bush 2009), with dispersal often limited to B2.5 m from the fruiting body (Ingold 1971;Yafetto et al 2008). Spores released from fungi growing on dung within the renvall (AKK D) might not arrive at AKK C, 15 m from the annex boundary.…”
Section: Coprophilous Fungal Spores As Indicators Of Land Usementioning
confidence: 99%
“…Based on this fact, some have hypothesized that some species could affect insects or perhaps that insects only act as host carriers of Basidiobolus species, especially mites (Ingold 1934;Werner et al 2012). The mechanism of conidium ejection is different from that of Conidiobolus (Ingold 1934; Yafetto et al 2008). In Basidiobolus spp.…”
Section: Taxonomic Description Of the Mammalian Pathogens Basidiobolumentioning
confidence: 99%
“…3Ac) (Dykstra 1994). The structure remains attached to the ejected conidium during the expulsion, but could be detached after landing (Ingold 1934;Yafetto et al 2008). Ingold found that the distance that Basidiobolus conidia traveled was between 1 and 2 cm (Ingold 1934).…”
Section: Taxonomic Description Of the Mammalian Pathogens Basidiobolumentioning
confidence: 99%
“…Recently, many biological material fractures have been highlighted: these fractures allow plants and fungi to disperse their seeds and spores, respectively [11][12][13][14][15], or corals to colonize new territories by their own fragmentation [16,17]. Mammals do usually not need fracture for moving: they can use instead their legs as springs and form a single projectile with their whole body [18].…”
Section: Introductionmentioning
confidence: 99%